Factors associated with cytomegalovirus (CMV) infection in neonates - Diar, Hitesh Amrat (My University, 2014)
Background: Congenital Cytomegalovirus (CMV) infection is common in neonates. Factors associated with congenital CMV infection in a human immunodeficiency virus (HIV) prevalent setting, are not known. Objective: To determine characteristics and outcome of congenital CMV-infected neonates. Methods: The Hospital records of neonates tested for CMV in first 21 days of life from January 2004 to December 2008 were retrospectively reviewed for the following variables; maternal and neonatal characteristics, clinical presentation, laboratory findings and in-patient mortality. Newborns that were CMV-positive and CMV-negative were compared for the above variables. Results: From the 177 patients suspected to have congenital CMV, 28 were confirmed to be congenital CMV-infected. The hospital records were retrieved for 24/28 (86%) CMV-positive and 62/149 (42%) CMV-negative patients (86 study participants). In CMV-positive group, 22 patients (92%) were low birth weight, 15 (63%) were preterm and 7 (29%) were small for gestational age. There were no significant differences noted for birth-weight, gestational age and growth between CMV-positive and CMV-negative patients. Hepatosplenomegaly was more common in CMV-positive than CMV-negative patients (n =9/24 (38%) vs n =10/62 (16%); p =0.03). The platelet count was lower in CMV-positive than in negative patients (median =71 x109/L vs median =49 x109/L; p =0.003). Congenital CMV-infected patients were more likely to be HIV-exposed (n =19/24 (79%) vs n =27/62 (44%); p =0.003) and HIV-infected (n =13/19 (68%) vs n =6/19 (32%); p =0.02) than CMV-negative patients. The in-hospital mortality was significantly higher in symptomatic congenital CMV-infected (n =10/24 (42%) vs n =11/62 (18%); p =0.01) and HIV co-infected (n =8/13 (62%) vs n =1/9 (11%); p =0.02) neonates. Conclusions: The presence of hepatosplenomegaly and/or persistent thrombocytopaenia in HIV-exposed patients is suggestive of congenital CMV with HIV co-infection. Neonates’ co-infected with HIV and CMV are less likely to survive to hospital discharge.